Місце норм адміністративного права в системі правових засад забезпечення діяльності закладів вищої освіти зі специфічними умовами навчання - Староста, В. І.; Starosta, V. I. (Європейські перспективи. - 2019. - №3. - С. 241-246, 2019)
З’ясовано, що правове регулювання юридичного забезпечення діяльності закладів вищої освіти зі специфічними умовами навчання представляє собою здійснюваний за допомогою норм права вплив на суспільні відносини, які виникають в межах діяльності відповідних структурних підрозділів ЗВО, з метою їх регулювання, упорядкування та забезпечення дотримання принципів верховенства права та законності. Доведено, що система правових засад юридичного забезпечення закладів вищої освіти зі специфічними умовами навчання представлена великою кількістю нормативних джерел, серед яких ключове місце належить нормам адміністративної галузі права.

Attention is focused on the fact that legal principles are usually interpreted in several contexts. So, on the one hand, legal principles are a system of principles, values and norms underlying the legal system or a specific field of law. On the other hand, legal principles should be interpreted as a system of normative legal acts, the norms of which are aimed at the legal regulation of social relations in a certain sphere of social life. It is noted that in the context of the problems presented in the article, it is most appropriate to talk about the second aspect of the specified scientific category. It has been found that the legal regulation of the legal support of the activities of higher education institutions with specific conditions of study represents the influence of the law on social relations that arise within the activities of the relevant structural subdivisions of higher education institutions, with the aim of their regulation, ordering and ensuring compliance with the principles of supremacy rights and legalities. It is proved that the system of legal foundations of legal support of institutions of higher education with specific conditions of study is represented by a large number of normative sources, among which the key place belongs to the norms of the administrative branch of law. This is explained by the fact that it is with the help of the norms of the relevant field of law: first, the general legal status of higher education institutions with specific study conditions is determined, as well as their structure, in which a prominent place is given to legal support departments; secondly, the status of subjects of legal support of higher educational institutions is established; thirdly, directions, tasks and functions of legal support departments are outlined, and hence the general purpose of their work.

Предложено авторское определение понятия правового регулирования юридического обеспечения учреждений высшего образования со специфическими условиями обучения. Выделена система нормативно правовых актов, нормы которых регулируют публичные дела в данной сфере. Доказано, что ключевое место в системе соответствующих правовых основ принадлежит нормам административного права.
Keywords: заклади вищої освіти зі специфічними умовами навчання; institutions of higher education with specific study conditions; заведения высшего образования со специфическими условиями обучения; юридичне забезпечення; legal security; юридическое обеспечение; норми адміністративного права; norms of administrative law; нормы административного права; правове регулювання; legal regulation; правовое регулирование